A Feminist Reading of Turkish Foreign Policy and the S-400 Crisis. Issue 4 (November 2021) - Akça Ataç, C.
Hypermasculine hegemonic masculinities have become the norm to dominate the foreign policies all around the world. As the populist foreign-policy visions, the byproducts of androcentric norm-creation, undermine the established rules for peace, diplomacy and co-existence in the international system, other experiences have faded away from the narratives that have defined and contributed to foreign policies. The accelerating urgency of the national security agendas of the hypermasculine states seek to cancel feminist definitions, practices and theories for the sake of physical force and state control. Nevertheless, more than any other period in history, it is these conflicting times that necessitate Cynthia Enloe's 'curious feminist' questions the most. Turkish foreign policy of the last decade has become a quintessential example of hypermasculine hegemonic masculinity, especially within the context of the S-400 crisis with the US, NATO and Russia; its feminist critics are distressingly rare. This paper aims to offer an alternative reading of Turkey's S-400 saga from a feminist perspective to contribute a Turkish case to feminist International Relations. First a definition of feminist International Relations will be provided. Then, the hypermasculine character of the Turkish hegemonic masculinity and its reflection on the current Turkish foreign policy will be analyzed. Lastly, the S-400 crisis of Turkey's decision to buy Russian defense missiles as a NATO member will be examined.